Immune-mediated acute neuropathies: an immunological analysis of patients hospitalized for Guillain-Barré syndrome in the years 2020-2021 at a university hospital in Vitória, ES, Brazil (Brazilian Journal of Health Research, 2023)
Introduction:When analyzing the increase in cases of Guillain-Barré Syndrome (GBS) admitted at a university hospital in Vitória, Es, Brazil, it was suggested to implement a simplified laboratory evaluation, widely available and low cost, which would allow the examiner to predict the risk of unfavorable evolution of the patient diagnosed with an Acute Immune-mediated Polyneuropathy. Objectives: Predict the greater severity of the patient with GBS at hospital admission, the unfavorable evolution of motor strength, in addition to the dependence on oxygen therapy, based on the laboratory analysis of the Total Neutrophils/Lymphocytes (NLR) ratio through the complete blood count (CBC). Methods: Patients with GBS and their admission CBC were evaluated. The data obtained was tabulated for statistical analysis with an appropriate small sample test. Results: NLR proved to be relevant and statistically significant as evidence of worse neurological status on patient admission and higher risk of death. Conclusion: There was statistical relevance of using NLR as an easily accessible and interpretable, besides widely available initial tool to contribute with the anamnesis and physical examination, providing more data for the examining doctor and allowing wide knowledge into the severity status of the patient with GBS.
Keywords: Guillain-Barré syndrome; Diagnostic techniques neurological; Patient acuity